Efektivitas Pemenuhan Putusan Restorative Justice: LPSK sebagai Instansi Pengawas - Tawang Amuhara Martha; Rexy Meidi Putra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
In Indonesia, restorative justice has begun to receive serious attention, as evidenced by the issuance of several regulations to support its implementation. One of these is the Juvenile Criminal Justice System Law, which incorporates the spirit of restorative justice into efforts to resolve cases involving children through the Diversion mechanism. However, despite the existence of supporting regulations, the implementation of restorative justice in Indonesia still faces various challenges. The purpose of this article is to examine the effectiveness of fulfilling restorative justice in Indonesia. The research results indicate that there are still several shortcomings in the enforcement of restorative justice. Additionally, there is a need for an institution capable of overseeing the implementation of non-litigation processes. The Witness and Victim Protection Agency is considered to have a strong position to act as a supervisor for restorative justice due to its alignment with its duties and functions.